1992
DOI: 10.1109/10.148386
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose response to stress hormone exposure in healthy man and insulin dependent diabetic patients: prediction by computer modeling

Abstract: To establish a qualitative and quantitative model of blood glucose response to stress hormone exposure, healthy subjects (HS) on and off somatostatin (250 micrograms/h) as well as insulin dependent diabetic patients were infused with either epinephrine (E), glucagon (G), cortisol (F), growth hormone (GH) or with a cocktail of these hormones raising plasma stress hormones to values seen in severe diabetic ketoacidosis. The developed input/output model consists of two submodels interconnected in series plus two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…insulin (groups A and C), causes peripheral insulin resistance but rather short-term hyperglycaemia, i. e. an acute increase in the glucose/insulin ratio. Thus, fasting glycaemia but not HbAlc values was related inversely to Mvalues (p < 0.001) and directly to HGP (p < 0.0001) for groups A, B, C and D. These findings are in line with the observation that fasting hyperglycaemia decreases glucose uptake in Type 1 diabetes [26] and determines blood glucose response to subsequent stress hormone exposure [27]. Similarly, correction of hyperglycaemia by 7 days of phlorizin administration has been shown to normalize peripheral insulin action in streptozotocin-diabetic rats, while low-dose insulin treatment at persistent hyperglycaemia was of no avail [28].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…insulin (groups A and C), causes peripheral insulin resistance but rather short-term hyperglycaemia, i. e. an acute increase in the glucose/insulin ratio. Thus, fasting glycaemia but not HbAlc values was related inversely to Mvalues (p < 0.001) and directly to HGP (p < 0.0001) for groups A, B, C and D. These findings are in line with the observation that fasting hyperglycaemia decreases glucose uptake in Type 1 diabetes [26] and determines blood glucose response to subsequent stress hormone exposure [27]. Similarly, correction of hyperglycaemia by 7 days of phlorizin administration has been shown to normalize peripheral insulin action in streptozotocin-diabetic rats, while low-dose insulin treatment at persistent hyperglycaemia was of no avail [28].…”
Section: Discussionsupporting
confidence: 84%
“…Some data suggest that glucose "toxicity" [29] operates even in the presence of normal or elevated basal serum insulin concentration and prevents insulin action from returning to normal. From this a decisive role has to be attributed to "acute glucose toxicity" [27,29,30] in the development of insulin resistance, which most likely results from any hyperglycaemic state, i.e. both in Type 1 and Type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it seems that cortisol [139] contributes to the dawn phenomenon in patients with Type II diabetes since deletion of cortisol secretion during the night with metyrapone, also decreased the early morning glucose excursion [140]. The correlation between EGP and cortisol [137] is also consistent with a 4 to 6 h delay in its action on glucose metabolism [141,142,143]. Other studies have shown an influence of sleep on subsequent glucose metabolism [144,145].…”
Section: Implications Of Revised Analysis In Type II Diabetessupporting
confidence: 67%
“…This was, however, not unexpected, since it has been considered that the relationship between stress and blood glucose response is essentially non-linear [17] and, furthermore, that the interrelationship between the different stress hormones is a complex one. Thus, previous studies on post-hypoglycaemic insulin resistance are not conclusive whether cortisol alone causes an impairment of the insulin sensitivity, whereas it clearly elicits an amplification of the GH effect in this situation [7,18].…”
Section: Discussionmentioning
confidence: 99%